Moving towards carbon neutral lifestyle through FinTech social media platform: a case study of Ant Forest - Shao, Zi; Xu, Yishuang (Frontiers in Environmental Science, 2023)
Introduction: The escalating environmental crisis resulting from high carbon consumption has led to severe consequences. Urgent measures to reduce carbon emissions are needed. Ant Forest integrates technology to promote low-carbon behaviors, but limited knowledge exists regarding its impact on environmental behaviors. Methods: This study constructed an integrated theoretical framework based on TRA, DIT, KAB, and RL. SEM analysis was conducted on survey data. Semi-structured interviews provided qualitative data on lifestyle changes. Results: Beliefs, norms, entertainment interaction, and commonweal significantly and positively impacted citizens’ use of Ant Forest. Knowledge sharing through Ant Forest promoted environmental attitudes and low-carbon behaviors. Discussion: This study shows how fintech social media can facilitate low-carbon lifestyles and provides inspiration for businesses and governments seeking to enable a low-carbon society. Limitations are the study’s reliance on self-reported data and constraints around generalizability. Further research should build on these findings.